Stabilizing austenite via a core-shell structure in the medium Mn steels. (June 2019) - Wan, Xinhao; Liu, Geng; Ding, Ran; Nakada, Nobuo; Chai, Yaw-Wang; Yang, Zhigang; Zhang, Chi; Chen, Hao
Abstract: Retained austenite plays a significant role in the strength-ductility balance of medium Mn steels. In this contribution, a new processing route (Flash-Austenite Reversion Treatment, Flash-ART) was proposed to design retained austenite with a compositional core-shell structure in an Fe-0.20C-7.76Mn-1.99Al (wt%) steel. It was interestingly found that the austenite core, which should transform into martensite based on its composition and size, was stabilized by the Mn enriched shell. Flash-ART allows us to obtain more retained austenite compared with the conventional ART. Graphical abstract: Unlabelled Image